Peran Sequence Paracoronal T2FSE Pada Informasi Citra Magnetic Resonance Imaging (MRI) Pelvis Pada Kasus Fistula - Ishry Ahsani Aulia Askar; I Putu Eka Juliantara; Edwien Setiawan Saputra (Pusat riset dan Inovasi Nasional, 2023)
The Role Of The T2FSE Paracoronal Sequence On Pelvic Magnetic Resonance Imaging (MRI) Image Information In Fistula Pelvic MRI is the most ideal part to be examined using Magnetic Resonance Imaging because it is very suitable for detecting abnormalities in the pelvis which most of the organs consist of soft tissue can be seen using MRI techniques . A fistula is an abnormal connection between two epithelial sites. A fistula is one that connects the anus with the skin around the anus or with other organs such as the vagina. One or more fistula bones are visible on the surface of the skin, which can become pus or feces during bowel movements. This study aims to determine the role of pelvic MRI examination with clinical fistula and to find out paracoronal sequence information can establish the clinical diagnosis of fistula. This study uses qualitative descriptive with a case study approach, the subject consists of one patient who will indeed perform a pelvic MRI examination with clinical fistula, the subject is carried out a 1.5 Tesla MRI examination to find out the sequence and procedure and sequence information used. The results of the study were obtained according to theory using sagittal sequences SE / FSE T2, axial SE / FSE T2, axial SE / FSE T1, coronal SE / FSE T2, and coronal GRE / SE / FSE T1, while in the field using sequences axial T2, axial Fat Sat, coronal T1, coronal T2, coronal T2 Fat Sat, sagittal T1 and sagittal T2 Fat Sat.